2016
DOI: 10.3389/fphar.2016.00182
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Treatment Protects against Brain Damage through an Anti-Inflammatory and Anti-Apoptotic Mechanism after Needle Insertion

Abstract: Convection enhanced delivery (CED) infuses drugs directly into brain tissue. Needle insertion is required and results in a stab wound injury (SWI). Subsequent secondary injury involves the release of inflammatory and apoptotic cytokines, which have dramatic consequences on the integrity of damaged tissue, leading to the evolution of a pericontusional-damaged area minutes to days after in the initial injury. The present study investigated the capacity for arctigenin (ARC) to prevent secondary brain injury and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 81 publications
(118 reference statements)
0
19
0
Order By: Relevance
“…Mice in the DMM group received a gavage of vehicle (0.5% CMC‐Na, a dietary cosolvent), while mice in the DMM + ATG group received oral administration of ATG (30 mg/kg, dissolved in CMC‐Na) daily for 8 weeks. This dose of ATG was prepared by adapting the procedure used in the previous study and our preliminary experiments. The mice were maintained in a temperature‐controlled room (20 ± 2°C) on a 12:12‐h light‐dark cycle and given free access to water and food.…”
Section: Methodsmentioning
confidence: 99%
“…Mice in the DMM group received a gavage of vehicle (0.5% CMC‐Na, a dietary cosolvent), while mice in the DMM + ATG group received oral administration of ATG (30 mg/kg, dissolved in CMC‐Na) daily for 8 weeks. This dose of ATG was prepared by adapting the procedure used in the previous study and our preliminary experiments. The mice were maintained in a temperature‐controlled room (20 ± 2°C) on a 12:12‐h light‐dark cycle and given free access to water and food.…”
Section: Methodsmentioning
confidence: 99%
“…This was observed in various colitis mouse models by the decreased activity of myeloperoxidase (MPO), eosinophil peroxidase (EPO), and cluster of differentiation 68 (CD68), indicators of neutrophils, eosinophils and macrophages, respectively [2,26,28] . In addition, AR reduced brain water content and hematoma and accelerated wound closure in convection-enhanced delivery induced brain injury in mice through regulation of various inflammatory factors and numbers of MPO-positive cells [28] . The anti-inflammatory effect of AR was first shown to be mediated through the suppression of NO production via inhibition of inducible nitric oxide synthase (iNOS) at both the expression and activity levels.…”
Section: Torreya Jackiimentioning
confidence: 99%
“…Cytokine-mediated feed-forward loops can amplify and coordinate this inflammatory response [15] . The anti-inflammatory effect of AR has been attributed to its potent in vitro and in vivo modulating effects on several important cytokines, such as tumor necrosis factor-α (TNF-α) [2,22,26,28,31,36,37] , interleukin-6 (IL-6) [2,26,28,29,31,37] , interleukin-1β (IL-1β) [2,29,37] , and interleukin-10 (IL-10) [2,28] . Inhibitory effects of AR on the expression levels of other cytokines, such as interleukin-2 and interferon-γ (IFNγ), were also found in vitro [3] .…”
Section: Torreya Jackiimentioning
confidence: 99%
“…Previous studies reported that ATG can inhibit intracellular ROS production by increasing hemeoxygenase-1 gene expression in rat primary astrocytes [12], and inducing endothelial nitric oxide synthase and attenuating subarachnoid hemorrhage-induced vasospasm through PI3K/Akt pathway in a rat model [13]. Arctigenin even has been shown to have a neuroprotective effect by mechanisms of anti-neuroinflammation and anti-oxidative stress [14]. It is unknown if ATG has a biological effect on myocardial ischemia/reperfusion-induced ventricular arrhythmias and if it exerts anti oxidative effects.…”
Section: Introductionmentioning
confidence: 99%